Emotional Geographic Conditions in the COVID-19 Era at SMAN 1 Pagaden - Ahmad Nurdin; Hani Chaerunnisa; Anwar Shidiq Santoso (research, training and philanthropy institution Natural Aceh, 2021)
Facing the COVID-19 pandemic, many habits or routines have changed. Activity restrictions are one of the efforts to prevent the spread of this pandemic. However, adapting to new habits is not an easy thing to do. As an adaptation to a new habit, temporary learning must be done online. Teachers and students experience many obstacles in doing online learning. So that a lot of research has been carried out to compile an effective and efficient online learning. However, research rarely reveals the emotional condition of teachers and students during a pandemic. Using descriptive qualitative methods, this study will reveal the geographic conditions of emotion at SMAN 1 Pagaden. The data were obtained through direct and indirect interviews, direct interviews were conducted with the teacher, while for students, a questionnaire was distributed using google form. The data is reduced and analyzed to get answers about the emotional condition of teachers and students at SMAN 1 Pagaden in the face of the pandemic. All data obtained after being analyzed will get solutions and ways to overcome the problems faced during this pandemic. With a research foundation that refers to Hargreaves' thoughts on the geography of emotions that limit questions to physical, socio-cultural, moral, professional and political elements